Arthritis alleviation: unveiling the potential in Abrus precatorius macerated oil - Sukanya Vijayan; Thirumal Margesan (Future Science OA, 2024)
Aim: This study endeavors to explore the anti-arthritic effects of macerated oil derived from the plant's aerial parts. Methods: The macerated oil was prepared using maceration in coconut oil, and its phytochemical composition was elucidated using GC-MS. To assess its anti-arthritic activity, in-vitro studies were conducted using various assays. Results & conclusion: The macerated oil showed better antioxidant and anti-arthritic potential by in-vitro investigations. Molecular docking studies elucidated potential binding interactions between specific constituents of the oil and critical molecular targets implicated in the pathogenesis of arthritis, further substantiating its therapeutic potential. The results demonstrated that Abrus precatorius macerated oil could ameliorate arthritis severity in a dose-dependent manner.